2014
DOI: 10.1155/2014/427298
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects ofGinkgo bilobaExtract EGb 761 against Noise Trauma-Induced Hearing Loss and Tinnitus Development

Abstract: Noise-induced hearing loss (NIHL) and resulting comorbidities like subjective tinnitus are common diseases in modern societies. A substance shown to be effective against NIHL in an animal model is the Ginkgo biloba extract EGb 761. Further effects of the extract on the cellular and systemic levels of the nervous system make it a promising candidate not only for protection against NIHL but also for its secondary comorbidities like tinnitus. Following an earlier study we here tested the potential effectiveness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 63 publications
3
26
0
3
Order By: Relevance
“…However, in some studies and clinical trials it has been stated that this herb has no beneficial effect in comparison with placebo in the treatment of tinnitus (Table 2). There are many studies on the effects of Ginkgo biloba in the treatment of patients with tinnitus that most of the findings of these studies are in contrast with each other; on the one hand, some of the studies reported that Ginkgo biloba is effective in the treatment of tinnitus effective [48][49][50][51][52][53] and on the other hand other studies referred to it as ineffective herbal medicine 28,[54][55][56][57] . The results of a systematic review showed that Ginkgo biloba is little/less effective in the treatment of tinnitus.…”
Section: Resultsmentioning
confidence: 99%
“…However, in some studies and clinical trials it has been stated that this herb has no beneficial effect in comparison with placebo in the treatment of tinnitus (Table 2). There are many studies on the effects of Ginkgo biloba in the treatment of patients with tinnitus that most of the findings of these studies are in contrast with each other; on the one hand, some of the studies reported that Ginkgo biloba is effective in the treatment of tinnitus effective [48][49][50][51][52][53] and on the other hand other studies referred to it as ineffective herbal medicine 28,[54][55][56][57] . The results of a systematic review showed that Ginkgo biloba is little/less effective in the treatment of tinnitus.…”
Section: Resultsmentioning
confidence: 99%
“…Нейропротективное действие EGb 761 обеспечивает повышение устойчивости нервной ткани к разнообразным повреждающим факторам. Так, в экспериментах на животных было показано снижение ототоксического воздействия цисплатина [41] и уменьшение повреждающего действия шума на слуховой анализатор [42,43] на фоне приема препарата. Указанные эффекты отражают процессы нейропластичности и позволяют объяснить аддитивный терапевтический эффект EGb 761 у больных с внезапной нейросенсорной тугоухостью, получающих лечение кортикостероидами, что было показано в рандомизированном контролируемом исследовании J. Koo и соавт.…”
Section: в помощь практическому врачуunclassified
“…Авторы другого экспериментального исследования исходили из посылки, что шум-индуцированное снижение слуха и коморбидный шум в ушах -весьма распространенные заболевания в наши дни [33]. Препаратом, показавшим эффективность при этой патологии в эксперименте, является EGb761.…”
Section: оториноларингологияunclassified